Epidemiological and Microbiome Characterization of Black Tooth Stain in Preschool Children - Zhang, Yu; Yu, Rui; Zhan, Jing-Yu; Cao, Gui-Zhi; Feng, Xi-Ping; Chen, Xi (Frontiers in Pediatrics, 2022)
Objective: To assess the epidemiologic attributes and microbial variations associated with extrinsic black tooth stain (BTS) among Chinese preschool children. Methods: This cross-sectional study included 250 preschool children (3-4 years) from three kindergartens in Shanghai, China. Following clinical examination, and using a case-control design, saliva and dental plaque specimens were collected from caries-free participants with (n=21, BTS group) and without (n=48, control group) BTS. The chi-square test and logistic regression model were used to evaluate factors associated with BTS. 16S rRNA gene pyrosequencing and metagenomics were used to characterize the associated microbial communities. Results: BTS was detected in 12.4% of participants, with a mean of 13.7 black-stained teeth. Participants with BTS had a lower caries burden and better oral hygiene (P=0.003). Children with less frequent intake of marmalade or honey (P=0.033) and regular application of fluoride (P=0.007) had a lower likelihood of having BTS. Microbiota analysis revealed 14 phyla, 35 classes, 63 orders, 113 families, 221 genera, 452 species, and 1771 operational taxonomic units (OTUs). In terms of microbial diversity, no significant differences were observed in the saliva of the two groups (P>0.05). Dental plaque from the BTS group exhibited higher OTU richness but lower evenness than that from the control group (Chao P=0.006, Shannon P=0.007, respectively) and showed a significant difference in β diversity (P=0.002). The microbiome in the two groups was characterized by various microbial biomarkers, such as Pseudomonas fluorescens, Leptotrichia sp._HMT_212, Actinomyces sp._HMT_169, and Aggregatibacter sp._HMT_898 in plaques from the BTS group. Functional analysis of the microbial species suggested the existence of a hyperactive metabolic state on teeth surfaces with BTS plaques and revealed that ferric iron, the iron complex transport system, and the iron (III) transport system were more abundant in BTS plaque samples. Conclusions: This study provides insights into the epidemiologic and microbial features of BTS in preschool children. The microbiome in BTS is characterized by various microbial biomarkers, which can serve as indicators for BTS diagnosis and prognosis.